Finacial Inclusion Profile In East Java - Ageng Asmara Sani (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
This study aimed the financial literacy, financial inclusion, and financial technology in East Java Indonesia. Financial inclusion is one of the ways of solving economic problems. Therefore, to out from financial exclusion and enter financial inclusion the people must increase their understanding of financial literacy and try to use financial services. This study will describe financial literacy with two dimensions (knowledge and application dimension), financial inclusion about accessibility in saving and loan and financial technology (receiving money and paying bills). The data used based on the Survey on Financial Inclusion and Access (SOFIA) 2017 with 6.873 respondents. The descriptive analysis was applied as an approach of assessment.  Finding on this research revealed that financial literacy, financial inclusion, using financial technology still very low especially in East Java. These results suggest that financial inclusion, financial literacy, and financial technology must be improving through supporting programs so that can parse the economic problems in society.